The Effect Of Family Characteristics And Parenting Patterns On The Nutritional Status Of Toddlers In Sigumpar Village, Sigumpar District, Toba Regency In 2020 - Munarni Munarni (International Journal of Basic and Applied Science, 2021)
Toddler age 12-59 months is a period when children really need nutrients in sufficient and balanced amounts. Lack of nutrients at this time can cause growth disorders. At this time too, the child is still completely dependent on the care and nurturing by his mother and family characteristics. The purpose of this study was to analyze the effect of family characteristics and parenting patterns on the nutritional status of children under five in Sigumpar Village, Sigumpar District. This type of research is a survey with the type of explanatory research. The population is all mothers who have children under five totaling 52 people. The collection of data on family characteristics, eating patterns using interviews guided by questionnaires and health parenting patterns using interviews guided by questionnaires. The nutritional status of children under five is based on the BB/TB index. Data analysis used multiple logistic regression test at a significance level of 95%. The results showed that the nutritional status of children under five (1-5 years old) based on the BW/TB index was normal (40.4%) and overweight (fat) 59.6%. Family characteristics consisting of knowledge of mothers in the good category 65.4%, higher education 75.0%, family income > 1,200,000 (100%), working mothers (59.6%), eating patterns applied by mothers to children good toddler 55.8%. Likewise, the health pattern of children under five is good 61.5%. There is an effect of parenting (eating and health) on the nutritional status of children under five.